Sexual dimorphism in the Turkmenian population in two types of dermatoglyphic traits : discriminant analysis - Karmakar, Bibha (Array, 2009)
Abstract: The aim of this study is to compare the pattern of sex differences between two different sets of dermatoglyphic traits (22 quantitative and 42 indices of diversity and asymmetry). Finger and palmar prints of Turkmenian population (547 individuals) were used for Multivariate analyses includes Cluster, Discriminant and Mantel test of matrix correlations. All variables (two groups) scattered into a number of small clusters those are markedly similar between males and females. These results were confirmed by Discriminant analysis – the two groups of variables are almost similar, the percentages of correctly classified individuals are 64.14% (22 traits) and 65.45% (42 traits); and Mantel statistics – the Z values are within the level of non-significance, very good similarities in 22 (0.95) and good similarities in 42 (0.87) traits. Sex dimorphism is similar between two categories of dermatoglyphic variables may be used for sex – discrimination in different populations